2017
DOI: 10.7554/elife.27417
|View full text |Cite
|
Sign up to set email alerts
|

Kinetochore inactivation by expression of a repressive mRNA

Abstract: Differentiation programs such as meiosis depend on extensive gene regulation to mediate cellular morphogenesis. Meiosis requires transient removal of the outer kinetochore, the complex that connects microtubules to chromosomes. How the meiotic gene expression program temporally restricts kinetochore function is unknown. We discovered that in budding yeast, kinetochore inactivation occurs by reducing the abundance of a limiting subunit, Ndc80. Furthermore, we uncovered an integrated mechanism that acts at the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
165
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 82 publications
(179 citation statements)
references
References 67 publications
8
165
0
Order By: Relevance
“…This was surprising considering that changes in transcript levels generally result in proportional changes in protein abundance (Spearman correlation of ~0.8 34,35 ). Recent studies have shown that upstream ORFs (uORFs) can have either a favourable or a deleterious effect on downstream mRNA translation [36][37][38][39][40] and suggested that the abundance of transcript is less important than the difference in translatability of the canonical versus ectopic transcript 38 . Thus, in situations wherein an upstream extension of the transcript leads to altered protein production, we speculate that this could be due to introduction of an uORF.…”
Section: Rnas From Ectopic Tsss In Nf-y Depleted Cells Undergo Translmentioning
confidence: 99%
See 1 more Smart Citation
“…This was surprising considering that changes in transcript levels generally result in proportional changes in protein abundance (Spearman correlation of ~0.8 34,35 ). Recent studies have shown that upstream ORFs (uORFs) can have either a favourable or a deleterious effect on downstream mRNA translation [36][37][38][39][40] and suggested that the abundance of transcript is less important than the difference in translatability of the canonical versus ectopic transcript 38 . Thus, in situations wherein an upstream extension of the transcript leads to altered protein production, we speculate that this could be due to introduction of an uORF.…”
Section: Rnas From Ectopic Tsss In Nf-y Depleted Cells Undergo Translmentioning
confidence: 99%
“…4d). Given that uORFs can modulate downstream translation and thus act as potent regulators of translation and protein expression [37][38][39][40]57 , it is conceivable that translation initiation from non-canonical start codon(s) within uORFs alters the reading frame and/or protein length; alternatively, it may affect the efficiency with which ribosomes translate the rest of the transcript 58 .…”
Section: Effects Of Uorfs Within Ectopic Transcripts On Protein Exprementioning
confidence: 99%
“…In addition to non-coding RNAs, mRNA isoforms have also been linked to transcriptional interference. For genes with more than one promoter, transcription from the distal promoter may not only produce a distinct mRNA isoform, but could also lead to the repression of an mRNA isoform transcribed from the open reading frame (ORF)-proximal gene promoter (Corbin and Maniatis, 1989;Moseley et al, 2002;Sehgal et al, 2008;Liu et al, 2015;Chen et al, 2017). In addition, since distinct mRNA isoforms may differ in their translational efficiency, regulation of promoter choice may impact gene expression at the protein level.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, since distinct mRNA isoforms may differ in their translational efficiency, regulation of promoter choice may impact gene expression at the protein level. In some instances, this difference in translational efficiency is due to the presence of upstream ORFs (uORFs) in the 5' leader of the distal promoter-derived mRNA isoform, which could inhibit translation of the protein-coding ORF (Moseley et al, 2002;Law et al, 2005;Sehgal et al, 2008;Ingolia et al, 2011;Rojas-Duran and Gilbert, 2012;Brar et al, 2012;Chew et al, 2016;Bird and Labbé, 2017;Chen et al, 2017;Cheng et al, 2018;Zhang et al, 2018) . As a result, in these cases, transcription of a distal promoter-derived mRNA isoform causes downregulation of protein expression through the integration of two seemingly disparate mechanisms of transcriptional and translational repression Cheng et al, 2018;Van Dalfsen et al, 2018;Hollerer et al submitted).…”
Section: Introductionmentioning
confidence: 99%
“…When the ∆2-28 or ∆11-19 mutant were combined with a 425 mutant that prematurely forms spindle microtubules in meiotic prophase (CUP-CLB3), 426we observed that sister chromatids, instead of homologous chromosomes, segregated 427in meiosis I (Figure 7E). The same phenotype occurs when Ndc80 is overexpressed in 428 meiotic prophase or when the LUTI-based repression of Ndc80 synthesis is disrupted 429(Miller et al 2012;Chen et al 2017). Therefore, the lack of Ndc80 turnover in meiotic 430…”
mentioning
confidence: 90%